Can Early Diagnosis of Varices, Regular Praziquantel, and Reduction of Hepatitis Coinfection Reduce Mortality among Patients Attended for Periportal Fibrosis in Northwestern Tanzania? A Case-Control Study - Daniel W. Gunda; Elizabeth F. Mtui; Semvua B. Kilonzo; Paulina M. Manyiri; David C. Majinge; Humphrey D. Mazigo (Journal of Parasitology Research)
Background. Schistosoma mansoni is highly endemic in the Lake Zone part of Tanzania and most people are chronically infected. Periportal fibrosis (PPF) is the commonest complication of chronic S. mansoni infection documented in up to 42% of studied participants in the community-based studies. These patients are at high risk of mortality since most of them are diagnosed late with bleeding varices. At Bugando, Schistosoma-related varices contributed to 70% of patients admitted due to vomiting blood with a two months’ mortality of over 10%. Earlier studies had reported higher mortality of up to 29% among patients with PPF even with the best in-hospital care. Understanding factors that increased the risk of mortality is important clinically in devising ways that can improve the outcome of this subgroup of patients. Methods. A retrospective analysis of patients with PPF from 2015 through 2018 was done. Their sociodemographic, clinical, laboratory, ultrasonographic, endoscopic, and survival status data were collected for analysis. STATA 13 was used for analysis, the prevalence of varices, active schistosomiasis, and hepatitis B coinfection was determined. Cumulative mortality as a major outcome was also determined, and factors associated with increased risk of mortality were assessed by a logistic regression model. Results. In total, 250 participants were included in this analysis. Majority, 222 (88.8%; 95% CI: 84.2-92.4) had active S. mansoni infection, and 40 (16.0%; 95% CI: 11.6-21.1) had S. mansoni-HBV coinfection. Cumulatively, 39 (15.6%; 95% CI: 11.3-20.7) patients died, with most deaths, 31 (79.5%; 95% CI: 63.5-90.7) occurring within two years following the diagnosis of PPF (chi2=6.3; p=0.012). The odds of mortality were independently associated with fishing (OR: 10.8; 95% CI: 2.2-52; p=0.003), upper gastro intestinal bleeding (OR: 2.4; 95% CI: 1.1-5.4; p=0.037), HBV coinfection (OR: 3.3; 95% CI: 1.2-91; p=0.019), and ascites (OR: 3.3; 95% CI: 1.3-8.2; p=0.010). Conclusions. In this, S. mansoni endemic area, varices, actives schistosomiasis, hepatitis B coinfection, and mortality are highly common. Screening for varices and initiation of prophylaxis, administration of praziquantel, and screening for hepatitis B should be part and parcel of care of these patients. The first two years of diagnosis, patients are at high risk of mortality; risk factors in this study should assist planning a closer follow-up of patients at risk of mortality to improve their long-term outcome.